A Production systems study on Grand Circuit Design Phils., Inc. - Bernales, Rolando; Bernarte, Alredo Jr.; Lachica, Edlyn S. (Diliman, Quezon City College of Engineering, 1997)
Grand Circuit Industry Philippines, Incorporated (GCI) was established in February of 1996. It is a wholly owned subsidiary of Malaysia Circuit Industry Sdn. Bhd. of Malaysia (MCI). GCI manufactures Consumer and Computer Grade Single-Sided Printed Circuit Boards (PCB) used for different appliances and electronic devices such as television , video recorders, calculators, and the likes. The plant is located inside Ledesma Compound in Barrio Patubig, Marilao, Bulacan. Its 3000 square-meter plant houses all of GCI's administrative, production and operations, marketing and sales, planning and quality control divisions. Presently, GCI is closely linked with Astec Power Inc. at the Economic Processing Zone Authority (EPZA) and Thomson Audio Phils. in Subic. GCI has produced different PCB types for various electronics companies, and continues to deal with such companies line Sony, Phils. and National Panasonic. A documentation of the company's existing system was done using their existing records and with added information from interviews with the division heads, production department heads, and operators. Analysis of the existing system showed that the company has problems regarding the following: 1. Poor production planning and control 2. Wrong attitudes of workers in the production area. 3. Delay in production output 4. No fix layout in Incoming Store. Using the tools in Capacity Planning, the group therefore recommended the following solutions: 1. Forecasting monthly demand - using moving average with period of three months, simply by averaging the demand for the last three months to get the forecast for the month. 2. aggregate production planning - for the next six months using the alternative of hiring additional operators 3. training and monitoring of workers 4. acquiring additional printing machine. At the end of this paper, the group has listed down several areas for further considerations and they are as follows: 1. generation of standard time for other models 2. design of faster and efficient buffer or collecting machine 3. design of better Incoming Store Layout 4. design a training program for workers.
IE 151
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Grand Circuit Industry Philippines, Incorporated; Electronics industry; Production engineering